Hydration and thermal strain during tennis in the heat - Bergeron, M. F. (British Journal of Sports Medicine, 2014)
Competitive tennis in the heat can prompt substantial sweat losses and extensive consequent body water and electrolyte deficits, as well as a level of thermal strain that considerably challenges a player's physiology, perception of effort, and on-court well-being and performance. Adequate hydration and optimal performance can be notably difficult to maintain when multiple same-day matches are played on successive days in hot weather. Despite the recognised effects of the heat, much more research needs to be carried out to better appreciate the broader scope and full extent of the physiological demands and hydration and thermal strain challenges facing junior and adult players in various environments, venues and competition scenarios. However, certain recommendations of best practices should be emphasised to minimise exertional heat illness risk and improve player safety, well-being and on-court performance.